Art and human nature xviii - Musso, Carlos G.; Enz, Paula A. (Revista del Hospital Italiano de Buenos Aires, 2014)
In his masterpiece “Impossible worlds”, Maurits Escher shows us that many people can share a single daily physical space and time, and yet be moving through different levels of consciousness, since every human being goes through a personal journey that is tailored to their emotional and intellectual understanding. This underlies the importance of tolerance as a guarantor of coexistence, as it comes to understand and accept the diverse nature of human conceptual paths
Keywords: planes of consciousness; Escher; impossible worlds